Migration Processes and East and Southeast Lithuania (1960–1980) - Stravinskienė, Vitalija (Genocidas ir rezistencija, 2015)
Based on archival and historiographical material, the author of the article examines the problem of migration in 1960–1980 in east and southeast Lithuania with the aim of answering the following questions: whether the east and southeast of the Republic of Lithuania was an attractive area for the residents of other districts of Lithuania and other Soviet republics to settle down in; what factors, causes and circumstances attracted them to the region; how migration processes affected the ethnic and demographic situation in the region; and whether the then administrative territorial reforms were favourable to the residents of this region.
Keywords: soviet occupation; migration; Eastern Lithuania; demographic